Cell Distribution within Yeast Colonies and Colony Biofilms: How Structure Develops - Plocek, Vítězslav; Váchová, Libuše; Šťovíček, Vratislav; Palková, Zdena (International journal of molecular sciences, 2020)
Multicellular structures formed by yeasts and other microbes are valuable models for investigating the processes of cell-cell interaction and pattern formation, as well as cell signaling and differentiation. These processes are essential for the organization and development of diverse microbial communities that are important in everyday life. Two major types of multicellular structures are formed by yeast Saccharomyces cerevisiae on semisolid agar. These are colonies formed by laboratory or domesticated strains and structured colony biofilms formed by wild strains. These structures differ in spatiotemporal organization and cellular differentiation. Using state-of-the-art microscopy and mutant analysis, we investigated the distribution of cells within colonies and colony biofilms and the involvement of specific processes therein. We show that prominent differences between colony and biofilm structure are determined during early stages of development and are associated with the different distribution of growing cells. Two distinct cell distribution patterns were identified-the zebra-type and the leopard-type, which are genetically determined. The role of Flo11p in cell adhesion and extracellular matrix production is essential for leopard-type distribution, because FLO11 deletion triggers the switch to zebra-type cell distribution. However, both types of cell organization are independent of cell budding polarity and cell separation as determined using respective mutants.
Keywords: Saccharomyces cerevisiae Proteins; cell adhesion; mutace; Saccharomyces cerevisiae; membránové glykoproteiny; yeast multicellular structures; buněčné dělení; mikrobiální interakce; colonies and biofilms; structure development; laboratory and wild Saccharomyces cerevisiae strains; Cell Division; Microbial Interactions; Biofilms; Membrane Glycoproteins; cell organization; Flo11p adhesin; Saccharomyces cerevisiae - proteiny; biofilmy; Mutation